High-Priority Information Technology Needs for Law Enforcement - Hollywood, John S. (RAND Corporation, 2015)
This study reports on strategic planning activities supporting the National Institute of Justice (NIJ) in the area of information technology, collecting and analyzing data on law enforcement needs and identifying potential solutions through technology assessment studies, extensive outreach and liaison activities, and subject matter expert panels.